Ulasan Teologis dari Kalimat “Bumi Belum Berbentuk dan Kosong, Gelap Gulita Menutupi Samudera Raya” dalam Kejadian 1:1-2 - Heppy Agustina Harefa; Yaudi Santos Santoso (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2024)
This journal discusses the meaning and implications of Genesis 1:1-2 in the context of the creation narrative. The main focus is on the primitive condition of the earth before God’s act of creation. Analysis was carried out on the biblical text and various theologians. The findings show that Genesis 1:1-2 describes an unstructured and empety initial state, which later became the foundation for the creation process. The creation narrative in Genesis 1:1-2 is one of the main foundations of Cristian theology. This research aims to dig deeper into the theological meaning of the phrase “the earth was formless and empty” in Genesis 1:1-2. The main focus is on the primitive condition of the earth before creation, and its implications for understanding God’s power and creativity. This research seeks to clarify various existing interpretations, especially regarding the concept of “tohu wabohu” and its relationship with other creation theories. A close analysis of Genesis 1:1-2 shows that the phrase “the earth was formless and empty” describes an intial state that was unstructured and without form. This condition is not the result of previous destruction, but is a “blank canvas” for God’s creative work. Thorugh His words, God transforms chaos into order, brings light into darkness, and creates everything from nothing. This research provides new contributions, namely: presenting a comprehensive review of various theological views regarding Genesis 1:1-2 including comparisons with other creation theories such as the gap theory, providing a deeper interpretation of the concept of “tohu wabohu” and clarifyng misunderstandings that often occur, highlights the implications of understanding the early conditions of the earth for our understanding of God’s power and creativity and the relationship between creator and creation.